Structures and Bonding in Hexacarbonyl Diiron Polyenes: Cycloheptatriene and 1,3,5-Cyclooctatriene - Min Zhang; Guangchao Liang (Chemistry, 2022)
Structural preferences of (1,3,5-cyclooctatriene) hexacarbonyl diiron [(C8H10)Fe2(CO)6] and cycloheptatriene hexacarbonyl diiron [(C7H8)Fe2(CO)6] were explored using density functional theory (DFT) computations. DFT computations together with experimental results demonstrated that structure with the [η3, (η1, η2)] mode is the preferred structure in (C8H10)Fe2(CO)6, and the [η3,η3] mode is preferred in (C7H8)Fe2(CO)6. For (C8H10)Fe2(CO)6, the conversion between the structures with [η3, (η1, η2)] mode and the [η3, η3] mode is prevented by the relatively high activation barrier. (C8H10)Fe2(CO)6 is indicated as a fluxional molecule with a Gibbs free energy of activation of 8.5 kcal/mol for its ring flicking process, and an excellent linear correlation (R2 = 0.9909) for the DFT simulated 1H-NMR spectra was obtained. Results provided here will develop the understanding on the structures of other polyene analogs.